Phylogenetic analyses of pandemic influenza A (H1N1) virus in university students at Tobetsu, Hokkaido, Japan - Inoue, Emi; Ieko, Masahiro; Takahashi, Nobuhiko; Osawa, Yoshiaki; Okazaki, Katsunori (Microbiology and immunology, 2012)
Pandemic influenza H1N1 virus (A[H1N1]pdm09) emerged in 2009. To determine the phylogeography of A(H1N1)pdm09 in a single population, 70 strains of the virus were isolated from university students or trainee doctors at Tobetsu, Hokkaido, Japan, between September and December 2009. The nucleotide sequences of the HA1 region of the HA genes and described phylogenetic relationships of the strains circulating among them were analyzed. It was found that the 70 isolates could be phylogenetically separated into three groups and that two epidemics were caused by different groups of the virus. The three groups were also distinguishable from each other by three amino acid changes: A197T, S203T and Q293H. The substitution of S203T, which is located in the antigenic site, suggests antigenic drift of the virus.